Предмет: Алгебра, автор: IngaNovikova

6(х-3)+8(х-4)=12(х-5)+3(х-1)

Ответы

Автор ответа: seronare8585
0
6x-18+8x-32=12x-60+3x-3                                                                                           6x-18+8x-32-12x+60-3x+3=0                                                                                        -x+13=0                                                                                                                          x-13=0                                                                                                                           x=13
Похожие вопросы
Предмет: Алгебра, автор: shuk26082018
Предмет: Математика, автор: Аноним
Предмет: Алгебра, автор: valera97978